Pengaruh Desain Produk, Citra Merek, dan Kualitas Produk terhadap Keputusan Pembelian Produk MS Glow di Kota Batam - Anisa, Rizqi; Evyanto, Winda (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study aims to examine the influence of product design, brand image, and product quality on consumer purchasing decisions for MS Glow skincare products in Batam City. The background of the problem lies in consumer hesitation driven by perceptions of monotonous packaging, inconsistent brand credibility, and quality inconsistency across product batches. The research employs a descriptive quantitative approach with purposive sampling, involving 100 respondents selected based on predetermined criteria. Data were analyzed using validity and reliability tests, classical assumption testing, and multiple linear regression analysis to evaluate both partial and simultaneous effects. The findings reveal that product quality exerts the most dominant influence on purchasing decisions (β = 0.707; p < 0.001), followed by brand image (β = 0.508; p = 0.001), and product design (β = 0.330; p = 0.015). Simultaneously, all three variables significantly influence purchasing decisions (F = 98.896; p < 0.001), with a coefficient of determination (R²) of 0.748, indicating that 74.8% of the variation in purchasing decisions can be explained by the model. These results highlight the importance for local skincare brands to consistently enhance design aesthetics, maintain brand credibility, and ensure stable product quality to strengthen customer trust and purchasing behavior.